Mr. Blue Sky [videorecording (DVD)] - Gurfield, Sarah; Lee, Tom Paddy; Kley, Chaney; Wolfe, Ashley Ara; Karn, Richard; Schellhardt, Mary Kate, 1978-; Wolfe, Nancy Rita (Bluesky Magic Productions, 2006)
This is a love story involving three friends: two girls, one born with Down syndrome, and one boy, who all grow up fighting how they are perceived by society.